Ascorbic acid oxidation in the non-enzymic browing of heat-treated 'kalamansi' (Citrus microcarpa bunge) juice - Lim, Jeansen S.
The major objective of this study is to find out whether or not the non-enzymic browning of heat-treated 'kalamansi' juice is due to the oxidation of ascorbic acid in the presence of oxygen, catalyzed by trace copper and iron naturally present in the juice. Freshly extracted 'kalamansi' juice was divided into four lots. A lot served as the control. Lot b1 was subjected to ion-exchange treatment and lot B2, to ion-exchange treatment and deaeration. Lot C was deaerated. Ion-exchange were done to remove from the juice as much trace metals and dissolved oxygen as possible. Freshly extracted juice and stored samples were analyzed regularly for ph, absorbance, hydrogen peroxide, dissolved oxygen, ascorbic acid and trace metals. The ascorbic acid degradation were identified through thin-layer chromatography. The coefficient of correlation and the coefficient of determination between absorbance and the presence loss of ascorbic acid was computed. The percentage loss of ascorbic acid was observed to be the least in lot B1, followed by lot B2. Lots A and C both had 100% loss of ascorbic acid by the thirty-seventh day of the storage period. The absorbance of lot A was highest at the end of the storage period, followed by lot C, then lot B1 and lastly, lot B2. Although furfural was found to be present in all lots on the fifth day, it was absent from lot A on the last day of the storage period. The loss of ascorbic acid was significantly correlated with lots B2 and B1. The correlation for lots A and C were lower. It appears that the non-enzymic browning of 'kalamansi' juice is due to the metal catalyzed oxidation of ascorbic acid by molecular oxygen. However, in the absence of most of the trace metals and dissolved oxygen, the non-enzymic browning might be due to the loss of ascorbic acid, but not by catalytic oxidation.